ESTIMATION OF DECREASING LOSSES OF ACTIVE POWER IN TRANSFORMERS IN SETTING BATTERY OF LOW-VOLTAGE CAPACITORS - V. N. Radkevich; M. N. Tarasova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
This paper describes an estimation method of decreasing losses of active power in power transformers with voltage 10(6)/0,4 kV after installation of devices of reactive power compensation on output side depending on voltage level, connected to capacity devices, taking into account dielectric loss in capacitors. Analysis of functional dependences was carried out. Investigation of function with a help of derivations was carried out. Points of function extremum and also its intervals of rise and fall rates were founded. This paper describes graphic investigation of obtained functional dependence, which is introduced by quartic polynominal. It is established that decreasing of losses of active power depends on technical parameters and load factor of transformer, coefficient of loading power of electricity consumers, voltage value connected to capacitor unit.Using obtained functional dependences, calculations for the main size-types of power transformers with voltage 10(6)/0,4 kV serie ТМГ 11 and ТМГ12 were done. It is established that depending on technical characteristics of certain transformer, coefficient of its loading and power, there is a definite value of deviation of real voltage value from working voltage of capacitor installation when it will be observed positive technical and economical effect from installed capacitor battery unit. For taken value of loading coefficient and transformer’s power the maximum decrease of losses of active power takes place under voltage directed to capacitor unit, which is lower then nominal value. For all taken size-types of power transformers the argument of investigating function for its maximal value is out of standard permissible of voltage deviations from nominal value.These functional dependents can be used for preliminary calculations, which are needed for making decision on compensation of reactive power in electric power supply systems of industrial objects. Their consideration allows more accurately evaluate technical and economical effect from installation of capacitor’s batteries in electrical networks with voltage up to 1 kV.